Sistem Monitoring SIRUS terhadap Efisiensi dan Kualitas Bangunan dalam Program BSPS di Kabupaten Bandung - Wardhani, Ghani Kusuma; Soekiman, Anton; R.P., Andini (Jurnal Talenta Sipil, 2025)
The Self-Help Housing Assistance Program (BSPS) aims to improve housing quality for low-income communities. However, the limitations of manual monitoring systems have caused inefficiencies and reduced building quality. This study evaluates the implementation of the Self-Help Housing Information System (SIRUS), a web-based digital technology, to enhance monitoring efficiency and building quality in BSPS projects in Bandung Regency. The research employs a quantitative survey method through questionnaires involving three respondent groups: PPK staff, field facilitators, and aid recipients. Data analysis was conducted using the SEM-PLS approach to identify the influence of related variables. The results indicate that SIRUS significantly improves monitoring efficiency, particularly through frequent use of the technology and its effective integration into workflow processes. Efficiency is influenced by human resource competencies and adequate training. In terms of building quality, SIRUS positively impacts outcomes, although its optimal implementation depends heavily on the technical skills of field facilitators and aid recipients' understanding of quality standards. Challenges such as limited information and communication technology infrastructure and insufficient technical training hinder SIRUS's effectiveness. In conclusion, the implementation of SIRUS contributes to enhancing efficiency and building quality in the BSPS program, with the caveat that continuous improvements in HR training and technological infrastructure support are essential. These findings provide strategic recommendations for stakeholders to improve housing quality through more comprehensive and inclusive digital technology integration.